Modern superconductive materials for electrical machines and devices working on the principle of levitation: Experimental Methods and Applications - Prikhna, T.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The peculiarities of high-pressure synthesis of highly dense nanostructural MgB2-based superconductive materials, of thermobaric treatment of MT–YBCO (melt-textured YBa2Cu3O7–d- based superconductor), high- ressure sintering of YBa2Cu3O7–d, oxygenation of MT–YBCO under high isostatic pressure of oxygen and processes of formation of superconductive junctions between MT-YBCO blocks are considered. The attained level of superconductive and mechanical properties of such materials and junctions make them promising for application in cryogenic devices working on the principle of levitation: electricmotors, generators, pumps for liquid-gas transfer, magnetic bearings, flywheels, fault current limiters, maglev transport, etc. High-pressure synthesized MgB2 (with Ti additions) blocks were for the first time tried in the superconductive electricmotor at 20 K and demonstrated an efficiency similar to MT–YBCO (at the same working temperature).